Impact of Virtual Navigation on the Education and Access of Patients with Cancer: A National Mixed Methods Investigation - Susan Haag; Joyce Schaffer (SAGE Publishing, 2024)
Introduction Despite growing evidence of efficacy, oncology patient navigation is not ubiquitously offered. Navigation may reduce barriers to cancer care, yet geographic location may limit patient access. To overcome geographical barriers and increase patient education in oncology, our medical center developed a virtual navigation program. Objective To examine the efficacy of the Virtual Navigation Program designed to increase patient access and education across local and national contexts Methods In this mixed-methods study, a total of 105 individuals completed an online survey administered nationally to oncology patients who used the navigation program. Clinical and demographic data were collected. Nonparametric tests were used for group comparisons (Wilcoxon Signed-Ranks test). Results Virtual navigation increased access as the majority of patients utilized the Virtual Navigation Program beyond the local area; 42% of patients were local; 58% were patients located across the US. 55 (52%) were female; 25% were non-White. Pancreatic cancer was the largest tumor type: 51 (49%). Patients agreed the virtual cancer education helped them make critical health choices (mean 4.89 SD = 84); understand their diagnosis (mean 4.44 SD = .77); were able to make informed decisions (mean 4.43 SD = .83), and empowered to manage their cancer care (mean 4.58 SD = .82). Post navigation, the user experience survey revealed significant increases in a subset of patients' cancer knowledge ( P  < 0.001), access to quality cancer education ( P  = 0.045), decision-making in cancer care (P < 0.05), and coordinated cancer care ( P  = 0.03). Conclusion This study explores a unique role that virtual navigation may play in helping accommodate healthcare for many cancer patients in underserved areas. The use of innovative aspects of research and education in virtual navigation may be successful in promoting patient empowerment in the cancer continuum. Internet-strategies are needed to inform sustainable patient navigation in low-resource contexts.